PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) TERHADAP PERKEMBANGAN SOSIAL EMOSIONAL ANAK KELOMPOK B DI TK NEGERI 1 BRANG ENE KABUPATEN SUMBAWA BARAT - Hesti Gustina Wardani; Ika Rachmayani; Fahruddin; Filsa Era Sativa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The social-emotional development of early childhood is an important aspect that requires attention in the learning process of early childhood education. To support this development, a learning model that stimulates active child engagement is needed, one of which is the Project Based Learning (PjBL) model. This study aims to determine the effect of the Project Based Learning (PjBL) model on the social-emotional development of Group B children at TK Negeri 1 Brang Ene, West Sumbawa Regency. This research used a quantitative approach with a quasi-experimental design. The sample consisted of 26 children, with 13 in the control group and 13 in the experimental group. Data collection techniques included observation and documentation. Data were analyzed using descriptive statistics and the Two Independent Sample Test. The results showed a t-value of 5.767 with a significance value of 0.001 < 0.005, indicating a significant effect of the PjBL model on children's social-emotional development. Therefore, it can be concluded that the implementation of the PjBL model has a positive influence on improving the social-emotional development of Group B children at TK Negeri 1 Brang Ene.